TDAH y su incidencia en el rendimiento académico de estudiantes de la UE Francisco Huerta Rendón, Babahoyo.2022 - Torres Sandoya, Naomi Gissela (2023)
Infants suffering from Attention Deficit Hyperactivity Disorders (ADHD) present difficulties in the learning process; reason for which, they have deficiencies in various areas affecting their academic performance and consequently their school evolution. Therefore, the development of this study has as its main objective to determine the way in which ADHD affects the academic performance of students from the EU Francisco Huerta Rendón. The present investigation has a methodology with a mixed approach; since, it has quantitative and qualitative implications, with a descriptive and explanatory scope; While the type of research was documentary, the inductive-deductive and analytical-synthetic methods were also used. To obtain relevant information, three investigative techniques were applied: the survey applied to 35 seventh grade students, the interview directed to three teachers of the institution and direct observation applied to both teachers and students to diagnose the level of academic performance of the learners. The results obtained with respect to the inferential analysis, determined that by means of the Rho Spearman correlation coefficient, there is a strong statistical association of -.838* between the two variables; that is, the higher the degree of Attention and Hyperactivity Disorder (ADHD), the lower the degree of academic performance of the students. Therefore, it is concluded that there is an inverse correlation between Attention Deficit Hyperactivity Disorder and the student performance of students in the seventh year of education at the Francisco Huerta Rendón Educational Unit.